2018
DOI: 10.1021/acs.analchem.8b00755
|View full text |Cite
|
Sign up to set email alerts
|

Shear Stress-Enhanced Internalization of Cell Membrane Proteins Indicated by a Hairpin-Type DNA Probe

Abstract: Shear stress is an important mechanical stimulus that plays a critical role in modulating cell functions. In this study, we investigated the regulating effects of shear stress on the internalization of cell membrane proteins in a microfluidic chip. A hairpin-type DNA probe was developed and indiscriminately anchored to the cell surface, acting as an indicator for the membrane proteins. When cells were exposed to shear stress generated from fluid cell medium containing external proteins, strong fluorescence was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 30 publications
0
17
1
Order By: Relevance
“…We herein propose that DONs with certain framework [ 39 ] could serve as an ideal scaffold for ADCs analogues with exceptional control over targeting ligand density and drug loading contents for optimized antitumor efficacies and safety profile. [ 40 ] Specifically, we construct a new prostate cancer (PCa)‐specific drug delivery system by introducing different numbers of ligand 2‐[3‐(1,3‐dicarboxy propyl)‐ureido] pentanedioic acid (DUPA) to a designed six‐helical‐bundle DNA origami nanostructure (6HB DON). DUPA has been demonstrated to be a high‐affinity inhibitor ( K i ≈ 0.02 × 10 −9 –0.1 × 10 −9 m ) for prostate‐specific membrane antigen (PSMA).…”
Section: Introductionmentioning
confidence: 99%
“…We herein propose that DONs with certain framework [ 39 ] could serve as an ideal scaffold for ADCs analogues with exceptional control over targeting ligand density and drug loading contents for optimized antitumor efficacies and safety profile. [ 40 ] Specifically, we construct a new prostate cancer (PCa)‐specific drug delivery system by introducing different numbers of ligand 2‐[3‐(1,3‐dicarboxy propyl)‐ureido] pentanedioic acid (DUPA) to a designed six‐helical‐bundle DNA origami nanostructure (6HB DON). DUPA has been demonstrated to be a high‐affinity inhibitor ( K i ≈ 0.02 × 10 −9 –0.1 × 10 −9 m ) for prostate‐specific membrane antigen (PSMA).…”
Section: Introductionmentioning
confidence: 99%
“…The caveolae-based internalization pathway contains ubiquitin ligase Smurf2 bound receptors and was proposed to shut down the BMP/TGFβ-SMAD signaling [ 91 ], while others showed that BMP-SMAD signaling could be initiated from receptors residing within caveolae [ 94 , 95 ]. Importantly, physical stimuli, such as substrate stiffness sensed by ECs, were sufficient to induce caveolin-dependent endocytosis of membrane receptors [ 96 , 97 , 98 ]. Mechanistically, ALK1 and BMPR2 localize within caveolae, while Alk1 physically interacts with caveolin-1 (cav-1) through cav-1′s scaffolding domain, suggesting a joint contribution of ALK1, BMPR2, and cav-1, as the key mediators of BMP9/10 signaling [ 99 , 100 , 101 ] ( Figure 1 f).…”
Section: Activating Versus Homeostatic Tgfβ/bmp Signaling In Endotmentioning
confidence: 99%
“…[ 72 ] Further, Lin and coworkers developed a cell surface‐anchored DNA probe for investigating the regulating effects of fluid shear stress on membrane protein internalization and the cell endocytosis process. [ 74 ] In addition to the different detection strategies of DNA‐CRNs demonstrated earlier for monitoring of the cellular microenvironment, DNA‐CRNs also play essential roles in cell‐based biocomputation, which has great potential in cancer diagnosis. [ 80 ]…”
Section: Detection Strategies Of Dna‐crns For Monitoring Of the Cellumentioning
confidence: 99%